Historical linguistics 2017 selected papers from the 23rd International Conference on Historical Linguistics, San Antonio, Texas, 31 July - 4 August 2017 - Drinka, Bridget, 1951- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2020)
"The collected articles in this volume address an array of cutting-edge issues in the field of historical linguistics, including new theoretical approaches and innovative methodologies for studying language through a diachronic lens. The articles focus on the following themes: I. Case & Argument Structure, II. Alignment & Diathesis, III. Patterns, Paradigms, & Restructuring, IV. Grammaticalization & Construction Grammar, V. Corpus Linguistics & Morphosyntax, VI. Languages in Contact. Papers reflect a wide range of perspectives, and focus on issues and data from an array of languages and language families, from new analyses of case and argument structure in Ancient Greek to phonological evidence for language contact in Vietnamese, from patterns of convergence in Neo-Aramaic to the development of the ergative in Basque. The volume contributes substantially to the debate surrounding core issues of language change: the role of the individual speaker, the nature of paths of grammaticalization, the role of contact, the interface of diachrony and synchrony, and many other issues. It should be useful to any reader hoping to gain insight into the nature of language change"--